1990
DOI: 10.1128/iai.58.9.3020-3028.1990
|View full text |Cite
|
Sign up to set email alerts
|

Mutants of staphylococcal toxic shock syndrome toxin 1: mitogenicity and recognition by a neutralizing monoclonal antibody

Abstract: Toxic shock syndrome toxin 1 (TSST-1), a 22-kilodalton protein made by strains of Staphylococcus aureus harboring the chromosomal toxin gene, may elicit toxic shock syndrome in humans. In vitro, TSST-1 induces T cells to proliferate and macrophages to secrete interleukin-1. To conduct a structure-function analysis, point mutations on the TSST-1 gene were generated by site-directed mutagenesis to identify amino acids critical for activity of the toxin. Specific tyrosine and histidine residues were replaced by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
28
0

Year Published

1991
1991
2000
2000

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 36 publications
4
28
0
Order By: Relevance
“…Initial studies of TSST-1 mutants revealed that residues on the back side of the central ␣-helix were required for the superantigenic activity of TSST-1 (20). For example, changing the histidine at position 135 to an alanine (H135A) resulted in the complete inactivation of TSST-1: H135A was neither lethal nor superantigenic (28, 29).…”
Section: Toxic Shock Syndrome Toxinmentioning
confidence: 99%
“…Initial studies of TSST-1 mutants revealed that residues on the back side of the central ␣-helix were required for the superantigenic activity of TSST-1 (20). For example, changing the histidine at position 135 to an alanine (H135A) resulted in the complete inactivation of TSST-1: H135A was neither lethal nor superantigenic (28, 29).…”
Section: Toxic Shock Syndrome Toxinmentioning
confidence: 99%
“…Other studies have not always concurred on these points. For example Pontzner et al (1989) found that N terminal peptides of SEA or SECl had weak T-cell stimulating activity whereas, contradictorily, Bohach et al (1989) and Blanco et al (1990) implicated the C terminal end of SECl or TSSTl, respectively, in activity. The reconciliation of these problems will come from the solution of the crystal structure of the toxin proteins.…”
Section: The Structure Of Bacterial Superantigensmentioning
confidence: 99%
“…Superantigens do not seem to engage the peptide-binding groove of MHC, however, nor do they act as peptides (Dellabona et al 1989). Unlike antigenic peptide/MHC, the complex of superantigen and MHC does not seem to engage all the variable components of the receptors on T cells; rather, the complex binds to a solventexposed face of V^e (Pullen et al 1990, Choi et al 1990, White et al 1992. Because superantigens bind TCRs via Vy?…”
Section: Introductionmentioning
confidence: 99%
“…One segment within the N terminal region of SEB governed the interaction of the toxin with MHC molecules; another segment governed the interaction with both MHC and TCR molecules, while a third segment selectively governed the interaction with the TCR. Unhke the case with SEB and related enterotoxins, the sites within TSST-l which govern the binding of this toxin to MHC and TCR molecules lie in the distal (COOH) half of the molecule (Edwin et al 1988, Blanco et al 1990). Additional site(s) at the N terminal region of the molecule may regulate the conformation of the molecule and provide sites for some neutralizing antibodies (Blomster-Hautamaa et al 1986).…”
Section: Residues Within the Staphylococcal Exotoxins Thai Govern Thementioning
confidence: 99%